Estimation of heterosis for yield and yield attributing traits in tomato crossed with line and tester method (Progressive Agriculture, 2019)
This study was conducted to estimate heterosis for the yield and yield contributing traits of 32 cross combinations involving 12 diverse lines of some Bangladeshi tomato genotypes considering line x tester mating fashion at the experimental field of Sher-e-Bangla Agricultural University, Dhaka in 2016-2017 and 2017-2018 winter season. The experiment was designed in a Randomized Complete Block Design (RCBD) with three replications. The analysis of variance (ANOVA) showed highly significant difference for all the characters suggesting the presence of genetic variability among the studied materials. Four cross combinations (L1xT1, L3xT2, L3xT3, L5xT1) showed desirable negative significant heterosis for days to first flowering in both relative heterosis (RH) and heterobeltiosis (HB) ranged from -2.56% to -19.05%, respectively. Highest positive significant heterosis in both RH and HB was observed in four crosses L4xT4 (63.48% and 48.25%), L5xT2 (46.77% and 46.27%), L5xT4 (62.58% and 34.78%) and L8xT3 (37.39% and 35.12%) for individual fruit weight (g), while six crosses L1xT2, L1xT4, L3xT2, L4xT4, L5xT4 and L6xT1 exhibited highest positive significant heterosis for yield per plant (kg) in both HB and RH ranged from 16.09% to 88.46% respectively. Heterotic hybrids with maximum number of studied desirable yield contributing traits (8) of both RH and HB were identified only two crosses L1xT2 and L4xT4.Progressive Agriculture 30 (2): 179-185, 2019